Personal nouns indicating food preferences - Batko-Tokarz, Barbara (Papers in Linguistics, 2024)
The article presents personal nouns associated with what a given person eats, a phenomenon that is becoming more and more popular nowadays in the Polish language. In order to emphasize current modifications in personal nouns, and to indicate both the continuity as well as the variability in the way they are created, the author provides crucial information regarding their functioning in the Polish language dictionaries from the 19th and 20th centuries. Thus, the first part of the article presents analogous old and new names of certain types of food- and drink-lovers, including those not eating meet and their opponents, but also new and unknown ways of creating them in the Polish language. In the second part of the article, the author analyses an interesting problem of metonymic or metaphoric use of people’s names created based on food items they typically eat. These names are often used to expressively name residents of other countries or to describe people of a certain personality or age associated with a particular type of food.